Sistem Informasi Surat Keterangan Pendamping Ijazah Berbasis Web Menggunakan Framework Laravel 10 Studi Kasus STIKOM El Rahma - Arman Sukmawan, Wendy Asswan Cahyadi, Suhendra Anjar Dinata (Jurnal Teknorama (Informatika dan Teknologi El Rahma), 2024)
This research aims to implement web-based information system technology for the Diploma Supplement (SKPI) at STIKOM El Rahma. Using the Research and Development (R&D), research method and the Waterfall system development method, the study seeks to maximaze technology application and solve exiting problems at STIKOM El Rahma. The system is built using PHP 8.3 programming language and Laravel 10 Framework, and is designed to facilitate the management of SKPI. The results of this research show that system is successful and effective in applying information system technology to the diploma supplement (SKPI) at STIKOM El Rahma. Keywoards : Information System, Diploma Supplement, Laravel 10, Research and Development, Waterfall, Web.